Research of Chamfering Tooth Crest of Spiral Bevel Gear based on Disc Cutter - Wei Wei; Zhang Lianhong (Jixie chuandong)
In order to solve low accuracy and inefficiency of tooth crest chamfering for spiral bevel gear,a method of tooth crest chamfering by using disc cutter is proposed. Gear solid model with the chamfering feature is established,crest lines are used as sweep path to create cylinder sweep volumes. Position relationship between gear and disc cutter is determined based on intersecting lines of cylinder sweep volumes,then machining parameters of chamfering are calculated. Simulation environment for chamfering is established including machine,disc cutter and gear,some groups of machining parameters are set to simulate machining process. The shape errors of chamfering are measured,optimized machining parameters are determined by aiming the minimization of shape errors. This method can be realized by installing disc cutter on gear milling machine which means special purpose machine is unnecessary. The disc cutter has longer cutting circumference compared to other shape cutter,which can prolong cutter life effectively.